3D FEM Soil-Structure Interaction Analysis for Kashiwazaki–Kariwa Nuclear Power Plant Considering Soil Separation and Sliding - Ichihara, Yoshitaka; Nakamura, Naohiro; Moritani, Hiroshi; Choi, Byunghyun; Nishida, Akemi (Frontiers in Built Environment, 2021)
In the 2007 Niigataken Chuetsu-oki earthquake, soil settlement, considered to be a result of the relative displacement between the soil and the structure, occurred alongside buildings at Kashiwazaki–Kariwa nuclear power plant. The objective of this study is to evaluate accurately the influence of the nonlinear behavior of the soil-structure interface on the response of the reactor building using a three-dimensional finite element model. To achieve this, we modeled the separation and sliding from sidewalls during a severe earthquake using joint elements, and evaluated the effect on the horizontal response of the structure. Through the soil-structure interaction analyses based on the recorded seismic data on the foundation for unit 7 reactor building using the three-dimensional finite element model, it was confirmed that the simulated horizontal responses of the building corresponded to the recorded seismic data. In addition, the comparison of the cases with and without separation and sliding revealed that the separation and sliding of soil from sidewalls reduces the embedment effects of the structure and that the reduction causes an occurrence of the foundation uplift. Moreover, in this study, it was clarified that the increase of the foundation uplift affected both the soil pressure characteristics beneath the foundation and along the sidewalls, and the maximum acceleration response of structures. In this study, the separation and sliding of soil from sidewalls had only a limited influence on the structural responses; however, under severe seismic excitation, it is expected that the embedment effects will be significantly reduced due to the separation and sliding of soil. Therefore, a precise response evaluation of the building including the nonlinear behavior due to separation and sliding should be considered in the seismic response analyses under severe seismic excitation.